Analysis of Students' Responses in the Mentoring of Qur'anic Reading Learning Using the Al-Hidayah Method - Moh. Miftakhul Ulum; Abdul Khamid; M. Miftakhul Huda; Abdulloh Safiq; Galuh Kartika Sari (Jurnal Pengabdian Masyarakat Al-Fatimah, 2025)
Allah Subhanallaahu wata’ala Allah SWT encourages reading the Qur'an slowly and with proper articulation (tartil), as stated in Surah Al-Muzzammil verse 4. However, many adolescents are still unable to read the Qur'an correctly and fluently, let alone understand its meaning. The Al-Hidayah method emerges as a practical and accessible approach to learning Qur'anic reading, characterized by the use of color-coded text in each volume. This study aims to describe students’ responses to Qur'anic reading instruction using the Al-Hidayah method. A quantitative approach with descriptive analysis was employed, utilizing questionnaires distributed via Google Form to 30 randomly selected students from SMPN 1 Trucuk Bojonegoro. The findings show that 73% of students responded very positively and 27% positively toward the use of the Al-Hidayah method. These results indicate the method's effectiveness based on the following indicators: 1) it is easy to understand and practice, 2) includes clear reading guidelines, 3) is practical to use, and 4) provides a highly positive learning experience. However, in practice, consistent training is still needed, particularly in mastering the nahawand recitation rhythm, to achieve optimal results.